Federalism: New Avenue for Nepal’s Development Diplomacy - Upadhyaya, Liladhar (NCWA Annual Journal, 2023)
Nepal has entered into a new governance model under the federal structure. It is a basic format of the new constitution assimilating federalism from its preamble to other relevant articles of the Constitution of Nepal. It is a new system for Nepal, and the nation should focus on enduring the system by rectifying lapses of federalism. It is criticized for being expensive and promoting means of corruption, but it can give positive results if we apply the principles and practices of federalism with due attention. As federalism is the basic guiding principle of the new political and constitutional context, the development diplomacy of the country should steer the path under the federal structure. Nepal's foreign policy is mainly guided by mutual respect territorial integrity and sovereignty; non-interference in each other’s internal affairs, respect for mutual equality, non-aggression, and the peaceful settlement of disputes, cooperation for mutual benefit, abiding faith in the Charter of the United Nations and value of world peace. Development diplomacy is also an expansion of these principles and practices for the prosperity of the nation. The ultimate goal of every form of diplomacy is to optimize national interest and promote world peace. Nepal has challenges as well as opportunities to get benefit from the means of development diplomacy under the federal system of governance. This article briefly talks about development diplomacy in the changed context of Nepal.